Multi-Purpose Open Space (MPOS) Evaluation to Support Inclusivity in Public Spaces PKOR Way Halim, Bandar Lampung - Septi Maulidyah; Rizka Nabilah; Martin Muljana (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
Public open spaces play a key role in sustainable urban development through their social, ecological, and cultural functions. However, their planning and design in many cities remain largely exclusive and have yet to fully incorporate inclusivity and sustainability principles. This study aims to evaluate the performance of the Way Halim Sports Activity Center (PKOR Way Halim) in Bandar Lampung as an inclusivity- and sustainability-based Multi-Purpose Open Space (MPOS) in supporting adaptive public spaces. The study uses a descriptive mixed-methods approach, combining a questionnaire survey of 100 purposively selected respondents with structured field observations. Data were analyzed using percentage-based descriptive statistics, categorized as low (<40%), moderate (40–60%), and high (>60%). The results show that social inclusivity, covering user diversity, spatial comfort, and activity flexibility, achieved high performance (64.8%–77%). In contrast, basic physical accessibility was low, particularly in disability-friendly facilities (38%) and adaptive lighting for visually impaired users (39.2%). Supporting facilities and user participation were rated moderate (42.8%–57%). PKOR Way Halim has strong potential to be developed as an MPOS but requires targeted design and policy interventions focused on universal accessibility. Strengthening public open space planning and management policies, including technical regulations for disability-friendly facilities, is essential to enhance its functionality and sustainability.